Comparison of Clinical Codes with Standards of Genitourinary Disease in Public Hospital of Sidoarjo - Fauzia, Vina; Nisak, Umi Khoirun; Cholifah, Cholifah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The accuracy of data diagnosis is important for clinical data management, reimbursement, andÂ issues related to healthcare and services. Based on preliminary observations, it was found that the inaccuracy of the diagnosis code maker with the genitourinary disease standard at theÂ Sidarjo District Hospital. The purpose of this study was to find out the comparison of coder clinical codes with genitourinary disease standards at the sidoarjo district hospital. The method used was quantitative with random sampling techniques presentedÂ in the form of frequency tables and cross tabulations and tested using the chi-square test. This study used medical records for inpatient genitourinary cases in 2022, Â with a total sample of 80 medical records. The results showed that completeness, timeliness,Â and accuracy had a significant influence on coding accuracy. Completness ( completeness ofÂ supporting information) obtained 58,8% complete medical record documents and 51.3% incomplete medical record documents (p=0.012). Accuracy (coding accuracy):52.5% of medicalÂ record documents were accurate and 47.5% of medical record documents were inaccurateÂ (p=0,0001). This study suggests improving the quality of coding by conducting coding trainingÂ and evaluating coding audits to support coding speed.